Monitoring and control of water-ecological space in the Dongting Lake region - Zeng, Zhiwei; Yang, Hua; Zhou, Hui; Lai, Nan; Song, Qidi; Ji, Qianfu; Ning, Qimeng (Frontiers in Environmental Science, 2023)
The territorial spatial planning in the new era strengthens the control of different functional spaces and emphasizes integrated and coordinated development of each functional space. Therefore, it is important to monitor the “structure-function” characteristics of water-ecological space based on the context of territorial spatial planning and develop a management and control framework. Based on land use and social statistics, and with the help of ArcGIS analysis, this paper examined the structure and function of the water-ecological space in the Dongting Lake study for 2010, 2015, and 2020, generating a control framework and proposing key initiatives. The main results are as follows: (1) The overall scale of the water ecological space in the Dongting Lake study is over 7300 km2. Water bodies had the largest share, followed by coastal terrestrial areas, while the land-water ecotone was the smallest. There was a small decrease in the water ecological space during the study period. Yueyang had the largest overall scale of water ecological space, while Linli had the smallest. (2) The comprehensive function of water ecological space in the Dongting Lake study was about 0.4000, increasing somewhat during the study period. Among the units, the comprehensive function value was highest in Yuanjiang City, while Jincheng City had the lowest. (3) From the structural elements of water ecological space, scientific planning of functional zoning of water ecological space should be carried out and combined with the delineation of “three zones and three lines”. Key initiatives such as multi-scale and multi-level planning and control, use control and access restrictions, determination of water ecological space ownership, pollution control and accountability, and comprehensive water ecological treatment and restoration should be promoted.